Earnings manipulation strategies during corporate financial failures: Evidence from Jordan - Abujassar, Monira (Asian Economic and Financial Review, 2025)
The purpose of this study is to examine the impact of pressure behaviors, specifically financial distress, on real earnings management activities. This study applies a data panel regression model. The hypothesis was examined by employing multiple linear regression and conducting robust regression on financial data from 48 industrial companies listed on the Amman Stock Exchange during the period of 2019 – 2023. The study employs a cross-sectional Roychowdhury model to assess real earnings management. The Z-Score model developed by Altman in 1968 is utilized to detect instances of corporate failure. The results indicate that financial distress leads to a marked rise in the practice of manipulating real earnings. This implies that as a company becomes less financially stable, the extent of manipulating real earnings through the management of production costs and discretionary expenses increases. However, the cash flow from operations indicates that financial distress has no significant effect. The study's conclusions have major implications for lenders, investors, and management, as financially unstable firms may manipulate earnings to obscure their true financial position. This analysis offers a more comprehensive understanding of the dependability of accounting data when evaluating the financial stability of a company.